APPLICATION OF STEM CELLS IN MEDICINE (International Conference on Modern Science and Scientific Studies, 2025)
Stem cell therapy represents one of the most promising advancements in modern medicine, offering potential solutions for a variety of diseases and conditions previously deemed untreatable. Stem cells have the unique ability to self-renew and differentiate into various specialized cell types, making them an attractive resource for regenerative medicine, tissue engineering, and disease modeling. This paper reviews the types of stem cells used in clinical applications, their mechanisms of action, and their therapeutic potential in treating neurological, cardiovascular, hematological, and musculoskeletal disorders. Challenges such as ethical concerns, immune rejection, and the risk of tumorigenesis are also discussed. Despite these challenges, ongoing advancements in stem cell research hold significant promise for the future of personalized medicine and regenerative therapies.